Holistic Nursing Practiced as Intensive Care Nursing - Joan M Fenske (Journal of Behavior Therapy And Mental Health, 2018)
This 11440 word manuscript relates a case study derived from field experiences. The format is unique. By describing the fictional character, the manuscript integrates a narrative story line. This is a case study portraying a fictional patient who is determined to take her life. Self distruction is overtly characterized. Holistic Nursing Practice emphasis is upon positive reinforcement.
Keywords: Holistic Nursing